Women’s Linguistic Features in Two Dramas - Aifi Umdatun Khoirot; Zuliati Rohmah; Desi Puspitasari (Nobel: Journal of Literature and Language Teaching, 2016)
The present paper aims at describing linguistic features of two women who have two different characteristics—feminine and less feminine—as apparent in “Who’s Afraid of Virginia Woolf” and “The Lover” dramas. Using Robin Lakoff’s (1975) women’s linguistic features, the research found out that not all features occur in the dialogues of the two female characters with other characters. Nine features were applied by Martha in “Who’s Afraid of Virginia Woolf” drama and seven features were used by Sarah in “The Lover.”  Based on the analysis of the data, it is uncovered that the use of the women’s linguistic features reflects uncertainty and lacking of confidence on the part of the women in their conversation.